2010 IEEE Global Telecommunications Conference GLOBECOM 2010 2010
DOI: 10.1109/glocom.2010.5683231
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Carrier-Sensing for Throughput Improvement in IEEE 802.11 Networks

Abstract: Abstract-As a Carrier Sense Multiple Access (CSMA) network, the performance of IEEE 802.11 networks highly depends on the accuracy of the carrier sensing procedure. However, conventional carrier sensing approaches suffer from the well known hidden and exposed node problems, adversely affecting aggregate throughput of the IEEE 802.11 networks. In this paper, we propose a novel scheme through which each station can adaptively select its Carrier Sense Threshold (CST) in order to mitigate the hidden/exposed node p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…However, if more of the process were to be implemented at a lower level by card manufacturers in hardware, the estimates may be more accurate since many of the obstacles we had to deal with could be avoided. Future work involves implementing this method in real-time and experimentally verifying the results of [9][10] [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if more of the process were to be implemented at a lower level by card manufacturers in hardware, the estimates may be more accurate since many of the obstacles we had to deal with could be avoided. Future work involves implementing this method in real-time and experimentally verifying the results of [9][10] [11].…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated the accuracy of our proposed estimation method via NS-2 simulations. Furthermore we have shown that these probability estimation techniques can be used to improve overall throughput by as much as 25% via packet length adaptation [10], 50% via carrier sense threshold adaptation [11], and 400% via modulation rate adaptation [9].…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…3) Adaptive Carrier-Sensing for Throughput Improvement in IEEE 802.11 Networks: Haghani et al [77] use periodic broadcast signals, from the AP, to facilitate adaptive carrier sensing in IEEE802.11 infrastructure-based networks. This approach dictates that all stations in a BSS must record their BUSY/IDLE (B/I) status during every time slot for a measurement period, ∆.…”
Section: A Adaptive Physical Carrier Sensing In Single Access Point mentioning
confidence: 99%
“…Since stations cannot accurately predict the channel status at the AP (due to problem nodes), each node uses both local and received B/I signals when determining the current availability of the channel in [77]. It is necessary for the AP to broadcast this information so that the stations in the BSS can choose their PCST such that the local BI signal mimics that of the AP.…”
Section: A Adaptive Physical Carrier Sensing In Single Access Point mentioning
confidence: 99%
“…Another benefit of implementing carrier sense is to improve throughput of wireless communication [33] [12]. Basically, they all leverage collision reduction property of carrier sense to improve channel utilization.…”
Section: B Motivation Of Csma/sfmentioning
confidence: 99%